UPAYA MENINGKATKAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR SHARE - Sri Puspitasari (JURNAL GLOBAL EDUKASI, 2019)
Abstract: The purpose of this study was to improve the learning outcomes of science students in class IX-1 of SMP Negeri 1 Meranti in the academic year 2018/2019. The variables studied were the understanding of the concept of human organ systems and student learning outcomes in science, using the type of Classroom Action Research. The sample in this study were all students of class IX-1 SMP Negeri 1 Meranti in the 2018/2019 Academic Year, amounting to 30 people. The research design used is as many as two cycles. The research instruments used in data collection were natural science learning achievement tests, student activity observation sheets and questionnaires about student responses. Data analysis techniques used are qualitative analysis and quantitative analysis. The results showed that there was an increase in the science learning outcomes of students who were taught using the Cooperative Learning Method of Think-Pair-Share Type. The average value of biology learning outcomes for Class IX-1 students of SMP Negeri 1 Meranti in the 2018/2019 Academic Year in the first cycle through evaluation tests was 86.66% and the average value in the second cycle was increased to 96.66%. While completeness student learning outcomes in the first cycle is 50% and in the second cycle increased to 88%. So the use of the Cooperative Learning Method Think-Pair-Share type can improve the learning outcomes of Natural Sciences-Biology class IX-1 students of SMP Negeri 1 Meranti in academic year 2018/2019. Keywords: think pair share, human organs  Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar IPA siswa kelas IX-1 SMP Negeri 1 Meranti Tahun Ajaran 2018/2019. Variabel yang diteliti adalah pengertian konsep sistem organ manusia dan hasil belajar IPA, dengan menggunakan Penelitian Tindakan Kelas (classroom Action Research). Sampel dalam penelitian ini adalah seluruh siswa kelas IX-1 SMP Negeri 1 Meranti Tahun Ajaran 2018/2019 yang berjumlah 30 orang. Desain penelitian yang digunakan yaitu sebanyak dua siklus. Instrumen penelitian yang digunakan dalam pengumpulan data adalah tes hasil belajar IPA, lembar observasi aktivitas siswa dan angket tentang tanggapan siswa. Hasil penelitian menunjukkan bahwa terdapat peningkatan hasil belajar IPA siswa yang diajar dengan menggunakan metode Cooperative Learning Tipe Think-Pair-Share. Nilai rata-rata hasil belajar biologi Siswa kelas IX-1 SMP Negeri 1 Meranti Tahun Ajaran 2018/2019 pada siklus I melalui tes evaluasi yaitu 86.66% dan nilai rata-rata pada siklus II yaitu meningkat menjadi 96.66%. Sedangkan ketuntasan hasil belajar siswa pada siklus I yaitu 50% dan pada siklus II meningkat menjadi 88%. Jadi penggunaan metode Cooperative Learning Tipe Think-Pair-Share dapat meningkatkan hasil belajar IPA-Biologi siswa kelas IX-1 SMP Negeri 1 Meranti Tahun Ajaran 2018/2019. Kata kunci:  think pair share, organ manusia